Natural languages: emergence and extinction - Chacón Sihuay, Jorge (1998)
When we speak of language emergence or language birth, we are not referring to the change of appearance and name of a language as a consequence of its uninterrupted, slow and gradual transformation, but rather to the emergence of a linguistic system -simple AND restricted- when it comes into contact for the first time with human groups speaking different languages. In the first case it is, in reality, a pseudo-birth of language, since we are not in front of a new linguistic system, but in front of the same language that has only changed its formal aspect and name.